2014
DOI: 10.3109/14767058.2014.968548
|View full text |Cite
|
Sign up to set email alerts
|

Use of lactoferrin in the newborn: where do we stand?

Abstract: Sepsis and necrotizing enterocolitis (NEC) cause significant morbidity and mortality in the newborn. Their ill effects persist in spite of appropriate and effective antibiotic therapy. Lactoferrin as an adjunct to antibiotics in the treatment of sepsis or NEC in the newborn may improve the clinical outcomes by enhancing the host defense and modulating the inflammatory response. This review focuses on the various aspects of lactoferrin use in the newborn.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…1 There are many interventions that have been implemented to decrease neonatal mortality and sepsis. [2][3][4][5][6][7][8][9] The majority of the neonatal deaths (99%) occur in low-and middle-income countries, out of which more than 50% neonatal deaths occur at homes, which lack adequate care. 10,11 The neonates of developing countries have intrauterine growth restriction too, which makes them further vulnerable to various neonatal morbidities and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…1 There are many interventions that have been implemented to decrease neonatal mortality and sepsis. [2][3][4][5][6][7][8][9] The majority of the neonatal deaths (99%) occur in low-and middle-income countries, out of which more than 50% neonatal deaths occur at homes, which lack adequate care. 10,11 The neonates of developing countries have intrauterine growth restriction too, which makes them further vulnerable to various neonatal morbidities and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…It has potent antimicrobial activity, can stimulate the innate immune system and promote epithelial proliferation and differentiation of the immature gut (213). Recent studies have identified LF supplementation as a promising agent for the reduction of late onset sepsis and necrotizing enterocolitis (214).…”
Section: Current Understanding Of Bpd Pathophysiology New Pathophysimentioning
confidence: 99%
“…Lactoferrin is an iron-binding glycoprotein typically found in human milk, saliva and other mucosal secretions and is produced by multiple cells, including neutrophils, during inflammation [ 5 , 6 ]. This apparent enrichment in secretions has been postulated to be related to lactoferrin’s broad antimicrobial properties [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Historically, these defense mechanisms were ascribed to lactoferrin’s iron sequestration properties [ 8 , 9 ]. However, more recent evidence suggests that lactoferrin may play a direct antimicrobial role by preventing bacterial biofilm formation, activating proteolysis of bacterial virulence factors and blocking the adhesion of bacteria to host immune cell membranes [ 6 , 10 ]. In fact, lactoferrin’s non-iron binding protein domains have exhibited frequent evolvement of polymorphisms, suggesting an importance of lactoferrin’s other moieties [ 11 ].…”
Section: Introductionmentioning
confidence: 99%